Effects of early vitamin D deficiency rickets on bone and dental health, growth and immunity. Issue 4 (7th April 2015) - Zerofsky, Melissa; Ryder, Mark; Bhatia, Suruchi; Stephensen, Charles B.; King, Janet; Fung, Ellen B.
Abstract: Vitamin D deficiency is associated with adverse health outcomes, including impaired bone growth, gingival inflammation and increased risk for autoimmune disease, but the relationship between vitamin D deficiency rickets in childhood and long‐term health has not been studied. In this study, we assessed the effect of early vitamin D deficiency on growth, bone density, dental health and immune function in later childhood to determine if children previously diagnosed with rickets were at greater risk of adverse health outcomes compared with healthy children. We measured serum 25‐hydroxyvitamin D, calcium, parathyroid hormone, bone mineral density, anthropometric measures, dietary habits, dental health, general health history, and markers of inflammation in 14 previously diagnosed rickets case children at Children's Hospital Oakland Research Center. We compared the findings in the rickets cases with 11 healthy children selected from the population of CHO staff families. Fourteen mothers of the rickets cases, five siblings of the rickets cases, and seven mothers of healthy children also participated. Children diagnosed with vitamin D deficiency rickets had a greater risk of fracture, greater prevalence of asthma, and more dental enamel defects compared with healthy children. Given the widespread actions of vitamin D, it is likely that early‐life vitamin D deficiency may increase the risk of disease later in childhood. Further assessment of the long‐term health effects of early deficiency is necessary to make appropriate dietary recommendations for infants at risk of deficiency.